DEVELOPMENT OF ATTACK PATTERN TRAINING VIDEO TUTORIALS IN INDOOR HOCKEY GAMES - Hendra Gunawan Siregar (Universitas Negeri Medan, 2022)
This study aims to overcome the boredom of the Indoor Hockey athletes in Binjai, Tanjung Balai, and Batu Bara in carrying out variations of attack pattern training in the Indoor Hockey game and increase the enthusiasm of the athletes with new variations of training. This research method is a type of research and development or Research and Development (R&D). The subjects of this study were taken from FHI Binjai, FHI Tanjung Balai, and FHI Batu Bara. The small group trial involved 12 people at FHI Binjai. The large group trial in this study involved 24 people at FHI Batu Bara and FHI Tanjung Balai. Variations of attack pattern training in this Indoor Hockey game have been created and validated by 3 experts, namely, Expert Coach, Expert Hockey, Media Expert. The results of the small group test involving 12 Binjai athletes, showed that the variation of attack pattern training in the Indoor Hockey game met the criteria to be continued in the large group trial with a percentage of 75 - 83%. The results of the large group test involving 24 athletes from the FHI Batu Bara, and Tanjung Balai, showed that the variation of attack pattern training in the indoor hockey game met the criteria to be continued in large group trials with a percentage of 85-92%. It can be concluded that the Development of Attack Pattern Training Video Tutorials in Indoor Hockey Games can be categorized very well with the meaning of being feasible and can be used. Because it is important in increasing the enthusiasm of the athletes to be more active in practicing attack patterns and as an attraction to overcome the boredom of athletes in Practice Indoor Hockey.Keywords: Video Tutorials, Attack Patterns, Hockey Indoor